Evaluation of the efficient use of water and production of potato crops under two irrigation techniques - Vargas Díaz, Ruy (2023)
Water is fundamental for the development of life, its care and good management being a responsibility that we must have when we use it. Therefore, the objective of this study was to evaluate the effects of two irrigation techniques on the yield and volume of water applied to the potato crop. For this, an experiment was established under two irrigation alternatives (proposed and traditional) in a potato cycle of the Tuquereña variety, in the municipality of Toca, department of Boyacá (Colombia). Where properties of each irrigation proposal were measured (uniformity of application, volume of water applied, irrigation efficiency) and at the end of the crop cycle, information on crop performance was taken. Statistically significant differences (p < 0.05) were presented when the proposed irrigation system was used, increasing production by 3 tons per hectare and reducing the volume of water applied to the crop by almost 40%, compared to traditional irrigation.